A New Era of Government Financial Management: A Case Study of Non-Cash Policies in Local Governments - Setiawan, Zeffri; Rosidi, R; Purwanti, Lilik (Riset Akuntansi dan Keuangan Indonesia, 2021)
This study aims to understand the implementation steps of non-cash transaction policies in the Central Java Provincial Government, with the Policy Implementation Theory from Edward III (1980) to analyze the supporting and inhibiting factors of implementation. The use of noncash as a transaction tool, there is still debate regarding the benefits and disadvantages of using non-cash transactions to the public. This research is descriptive qualitative research with a case study approach. The results showed that the implementation of the non-cash policy in the Central Java Provincial Government carried out the following steps: preparation, implementation, control. Supporting factors in implementation come from communication and financial resources. Meanwhile, human resources, physical resources, dispositions, and bureaucracy need to be evaluated because they can hinder implementation in the Central Java Provincial Government. Research shows that the implementation of the non-cash transaction policy has been going well in terms of the implementer’s understanding of non-cash administration.